Strategic Marketing, Innovation Culture and Competitive Advantage of Selected Petroleum Products Marketing Companies: Evidence from Nigeria - D. Adefulu, Adesoga; U. Ashikia, Olalekan; G. Makinde & Abiodun E. Alao, Olubisi (British Journal of Marketing Studies, 2021)
This paper investigated the effect of strategic marketing (SM) on innovation culture (IC) and competitive advantage (CA) of selected petroleum products marketing companies in Lagos State, Nigeria. It further examined relative moderating role of resource capabilities (RC). A cross-sectional survey research design was used in the study. Target population comprised 1568 managerial staff of the selected companies. Cochran’s formula was used to determine a sample size. Stratified random sampling and proportionate sampling techniques were used to group the sample to definite categories of directors, senior managers, marketing managers and supervisors and for adequate representation. A validated questionnaire was administered and a total of 497 retrieved for analysis. The data collected were analysed using multiple regression analysis. The findings revealed that strategic marketing had a positive and significant effect on innovation culture (Adj.R2= 0.390, F (1, 491) = 80.180, p < 0.05) and competitive advantage (Adj.R2 = 0.627, F (4, 491) = 208.685, p < 0.05). The study recommended that the management of petroleum products marketing companies should be committed to adopting strategic marketing towards building innovation culture and achieving competitive advantage.